2015
DOI: 10.5194/amt-8-3087-2015
|View full text |Cite
|
Sign up to set email alerts
|

The Ice Selective Inlet: a novel technique for exclusive extraction of pristine ice crystals in mixed-phase clouds

Abstract: Abstract. Climate predictions are affected by high uncertainties partially due to an insufficient knowledge of aerosolcloud interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…One reason it can be misleading to equate ice residuals with INPs is that MPCgenerated ice crystals can contain cloud condensation nuclei (CCN) which have been collected upon riming but have not acted as INPs. One possibility of overcoming this issue is to sample ice residuals of freshly formed, small ice crystals (< 20 µm), which are assumed to have grown by the initial phase of vapour diffusional growth only (Mertes et al, 2007;Kupiszewski et al, 2015). On mountaintop stations, where such crystals can be collected in-cloud, however, hoar frost (cloud droplets frozen onto surfaces) can be a strong source of small (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One reason it can be misleading to equate ice residuals with INPs is that MPCgenerated ice crystals can contain cloud condensation nuclei (CCN) which have been collected upon riming but have not acted as INPs. One possibility of overcoming this issue is to sample ice residuals of freshly formed, small ice crystals (< 20 µm), which are assumed to have grown by the initial phase of vapour diffusional growth only (Mertes et al, 2007;Kupiszewski et al, 2015). On mountaintop stations, where such crystals can be collected in-cloud, however, hoar frost (cloud droplets frozen onto surfaces) can be a strong source of small (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Following field measurements at the Jungfraujoch, Cozic et al [2008] and Mertes et al [2007] reported enrichment by mass of BC in IR based on particle soot absorption photometer (PSAP) measurements, while Ebert et al [2011] found enrichment by number of C-O-S particles (i.e., internal mixtures of organics, nitrates, and sulfates, sometimes containing soot inclusions) in IR relative to the interstitial aerosol using scanning electron microscopy and transmission This paper focuses on measurements of the physical properties and BC content of IR sampled using the Ice-CVI during the joint CLACE 2013 and Ice Nuclei Research Unit (INUIT) campaign. The campaign was conducted at the high-alpine research station Jungfraujoch in the winter of 2013 with the principal goals of investigating the characteristics of INP [Boose et al, 2016;Kupiszewski et al, 2015;Worringen et al, 2015] and cloud microphysical properties [Lloyd et al, 2015;Vochezer et al, 2016]. Based on an analysis of IR size distributions measured downstream of the Ice-CVI, the size of particles predominantly acting as INP in MPCs is determined.…”
Section: Introductionmentioning
confidence: 99%
“…At present, these effects are difficult to parameterize in models due to a lack of observational research on formation, properties, and phase partitioning (Kamphus et al, 2010;Shupe et al, 2006). This has resulted in a global effort to study these clouds (Abel et al, 2014;Davis et al, 2007a;Hiranuma et al, 2016a;Kupiszewski et al, 2015;Mertes et al, 2007;Patade et al, 2015).…”
Section: Introductionmentioning
confidence: 99%